Facilitators and barriers for using outdoor areas in the primary work tasks of eldercare workers in nursing homes - Sandra Schade Jacobsen; Maja Vilhelmsen; Lene Lottrup; Mikkel Brandt (BMC, 2023)
Abstract Background Eldercare workers in nursing homes report high musculoskeletal disorders, stressful work, and sickness absence. Initiatives that can accommodate these issues are needed. Current studies point out that nature contact may offer a range of human health benefits, potentially promoting healthier work among eldercare workers. Therefore, this study aimed to investigate facilitators and barriers for using outdoor areas as part of the daily work among eldercare workers in Danish nursing homes. Methods In this multiple case study, we collected data from three nursing homes, conducting three semi-structured focus group interviews with eldercare workers and three individual interviews with nursing home managers. Furthermore, we conducted observations of the daily work and mappings of the nursing homes' outdoor environments to gain in-depth knowledge of eldercare workers' and managers' perspectives on using outdoor areas in their daily work. The data was thematically analysed using 'The Behaviour Change Wheel' (BCW), more specifically the COM-B model, as a theoretical foundation for exploring facilitators and barriers for the use of outdoor areas. Results Frequently mentioned facilitators were facilities, traditions or repetitive events, positive experiences with residents ('star moments'), and knowledge about the residents. Frequently mentioned barriers were insufficient staffing, hierarchy in the work tasks, professional identity, and lack of ideas. Conclusions The identified facilitators and barriers should be considered when designing initiatives for increased use of outdoor areas or activities of eldercare workers. Trial registration According to the Danish ethics committee (Law of committee, (komitéloven) paragraph 14, Sect. 2), qualitative interviews, which do not include human biological materials, do not need neither approval by ethical and scientific committee or informed consent (The Danish National Centre for Ethics).